2021
DOI: 10.3390/plants10010105
|View full text |Cite
|
Sign up to set email alerts
|

Metabolome Analysis Revealed the Mechanism of Exogenous Glutathione to Alleviate Cadmium Stress in Maize (Zea mays L.) Seedlings

Abstract: Cadmium (Cd) is one of the major heavy metal pollutants in the environment and imposes severe limitations on crop growth and production. Glutathione (GSH) plays an important role in plant Cd tolerance which is able to scavenge stresses-induced reactive oxygen species (ROS) and is involved in the biosynthesis of phytochelatins (PCs). Our previous study revealed that Cd stress affects maize growth, and the GSH treatment could relieve Cd stress in maize seedlings. In this study, we attempted to characterize the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Besides increasing enzymatic activities and upregulation of GSH biosynthesis gene expressions, exogenous GSH plays a significant role in regulating photosynthetic activities ( Wang et al, 2011 ; Khan et al, 2016 ; Li et al, 2021 ). Wang et al (2021) carried out a greenhouse hydroponic experiment using two different barley genotypes, Cd-sensitive Dong 17 and Cd-tolerant Weisuobuzhi, to investigate the effects of exogenous GSH on their photosynthetic performances under Cd stress. It was revealed that the treatment of GSH significantly increased both genotypes, especially Cd-sensitive Dong 17, with a great increase in parameters such as the net photosynthetic rate, stomatal conductance, transpiration rate and photochemical efficiency (F v /F m ) by 130.2, 68.9, and 52.4%, respectively, when compared to the control plant ( Wang et al, 2011 ).…”
Section: Roles Of Exogenous Gsh In Stressed Plantsmentioning
confidence: 99%
See 3 more Smart Citations
“…Besides increasing enzymatic activities and upregulation of GSH biosynthesis gene expressions, exogenous GSH plays a significant role in regulating photosynthetic activities ( Wang et al, 2011 ; Khan et al, 2016 ; Li et al, 2021 ). Wang et al (2021) carried out a greenhouse hydroponic experiment using two different barley genotypes, Cd-sensitive Dong 17 and Cd-tolerant Weisuobuzhi, to investigate the effects of exogenous GSH on their photosynthetic performances under Cd stress. It was revealed that the treatment of GSH significantly increased both genotypes, especially Cd-sensitive Dong 17, with a great increase in parameters such as the net photosynthetic rate, stomatal conductance, transpiration rate and photochemical efficiency (F v /F m ) by 130.2, 68.9, and 52.4%, respectively, when compared to the control plant ( Wang et al, 2011 ).…”
Section: Roles Of Exogenous Gsh In Stressed Plantsmentioning
confidence: 99%
“…Apart from the uptake and distribution of HM, metabolomics, which is the study of the identification, quantification, and distribution of metabolites, such as sugars, alcohols, amino acids, organic acids, and polyamines, provides a better understanding of the plant’s responses to any interference, including HM stresses ( Ghatak et al, 2018 ). In the metabolome study of maize leaves under Cd stress, the tricarboxylic acid (TCA) cycle-related metabolites such as malic acid and maleic acid were found to be decreased in leaves, possibly due to the nature of its enzyme known as fumarate hydratase, that was reported to be particularly sensitive to ROS ( Lushchak, 2011 ; Wang et al, 2021 ). With the addition of GSH, the trend of the TCA cycle-related metabolites was reversed, where malic and maleic acid levels were detected to increase in leaves, implying that the exogenous GSH successfully alleviates the oxidative stress induced by Cd toxicity on the TCA cycle ( Wang et al, 2021 ).…”
Section: Roles Of Exogenous Gsh In Stressed Plantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Understanding the complexity of the mechanisms responsible for ovary and silk development and how waterlogging and shading stress cause ovary abortion is critically important to improve maize production. Metabolomic studies have unraveled some mechanisms underlying kernel development ( Wen et al, 2014 ; Yang et al, 2018 ; Bernardi et al, 2019 ; Gálvez Ranilla, 2020 ) and the responses of different crop varieties to various abiotic stress ( Obata et al, 2015 ; Sun et al, 2016 ; Xiong et al, 2019 ; Wang et al, 2021 ). The reasons for maize ovary/kernel abortion in response to abiotic stress are very complex.…”
Section: Introductionmentioning
confidence: 99%